Influence of organizational culture in the relationship between information system and operational performance on manufacturing sector in UAE - Abdulla Lari, Darwish Ahmed Darwish (2021)
The manufacturing industry plays a very vital role in the economic growth and development of many countries including UAE. One of the important performance criteria in manufacturing is organizational performance (OP), which relates to the utilization of all resources (people/assets/time) to deliver lower cost and higher quality products, services to the customers in the shortest time possible. The operational performance depends on information system (IS) in many ways, such as through industrial technology applications or/and through its multiple administrative applications such as measuring the return on investment (ROI) and return on assets (ROA), relative profitability, economic input and outputs, total revenue and others. The literature review indicates that there is no much researches on the role of IS on operational performance and also its roles to lead to operational performance in the UAE manufacturing industry. Hence, this research aimed at investigating the role of Information System on the Operational Performance of Manufacturing Companies in the UAE. The study adopted a quantitative approach where the data was collected by administering questionnaires to 250 operation staff of Abu Dhabi manufacturing companies. However, 205 of the questionnaires were returned, and only 200 are valid which indicates a response rate of 80%. The collected data was analysed descriptively using SPSS and AMOS software to determine the critical factors of information system dimensions and also in operational performance. Ultimately the data was used to develop the relationship between information system dimensions and operational performance together with the organizational culture as mediators in the relationship. The findings from the descriptive analysis showed that the most critical factor for information system dimensions is the ease of use, and for operational performance is flexibility. While for multivariate analysis found that TPS has positive but not significant effect to OP; OIS has positive but not significant effect to OP; FMW has a positive and significant effect on OP; DSS has a negative and not significant effect to OP and OP has positive but not significant effect OC. For the path relationship between the four exogenous variables (TPS, OIS, DSS, and FMW) and the mediator variable (OC), the results are TPS has positive and significant effect to OC; OIS has positive but not significant effect to OC; FMW has positive and significant effect to OC and DSS has positive and not significant effect to OC. Collectively, the five exogenous constructs (TPS, OIS, DSS, FMW and OC) explained 89% variation in operational performance and 86% of the variation in organisational culture. However, for a mediator, it was found that OC has no significant mediating effect on the relationship between TPS and OP; OC has no significant mediating effect on the relationship between OIS and OP; OC has no significant mediating effect on the relationship between DSS and OP and OC has no significant mediating effect on the relationship between FMW and OP. It can be concluded that there is a positive relationship between information system dimensions and operational performance. However, organizational culture has no contributing any mediating effect to the relationship, which shows that manufacturing companies in the UAE need to pay more attention to improve IS, since it is more essential than OC to improve OP. These findings have contributed to the body of knowledge and could be shared among the UAE manufacturing practitioners.